Glencoe mathematics : - Collins, William (Glencoe/McGraw-Hill, 2001)
This book is designed to help middle school students develop mathematical power. the ability to use what they know and to give them a good start into higher level mathematics. This text also helps students learn reasoning skills, make connections to the real world, become expert problem solvers, and explain their work to others.